TRANSFORMASI SISTEM INFORMASI AKUNTANSI MENUJU SISTEM INFORMASI AKUNTANSI DIGITAL PADA UMKM KLASTER MBANGUN MAKUTOROMO - Ika Swasti Putri; Endang Saryanti; Siti Hayati Efi Friantin; Tri Nurdyastuti (Sekolah Tinggi Ilmu Ekonomi AMA, 2022)
An Accounting Information System (AIS) involves the collection, storage, and processing of financial and accounting data used by internal users to report information to investors, creditors, and tax authorities. It is generally a computer-based method of tracking accounting activities in relation to information technology resources. .SIA combines traditional accounting practices with modern information technology resources. In the past, accounting records used manual methods, but over time, most AIS currently use accounting automation processes. The purpose of this community service is to maximize technology in the Mbangun Makutoromo Cluster UMKM by providing solutions in the form of: 1 Assistance in making manual bookkeeping, 2. Assistance in the use of smartphones for bookkeeping applications. The service will be carried out in 2021. The data collection method is through interviews, observation and documentation. The method of implementing the activities is carried out by means of training and mentoring.